2018
DOI: 10.23851/mjs.v28i2.504
|View full text |Cite
|
Sign up to set email alerts
|

Affect the Cross Linking Degree and Polymer Composition on the Mechanical Properties of Poly (vinyl alcohol)/ Pullu-lan Films

Abstract: In this study Cross-linked PVA/Pullulan film was prepared. Cross-linking reaction done by addi-tion of gluteraldehyde at different reaction time (10,30and 60) min. Chemical interaction, me-chanical, thermal properties, water solubility and film morphology was studied for cross-linked PVA/Pullulan, PVA and Pullulan only. Thus FTIR investigated formation of hydrogen bonding between pullulan and PVA with (GA). Tensile strength, tensile modulus and elongation (%) at break for PVA/Pullulan film was improved with ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The effects of different crosslinking degrees on the mechanical properties of PU‐D‐x films were investigated, and the results are shown in Figure 3. It can be seen that as the amount of crosslinking agent increased from 0.3% to 1.2%, the tensile strength of PU increased from 3.11 to 17.08 MPa, while the elongation at break decreased from 1350% to 669%, this is because that higher cross‐linking degree increases the cohesive energy density, restricts the mobility of polymer chains and limits the deformation and destruction of polymer chains, which leads to the deformation and destruction of PU requires greater external force 26,27 …”
Section: Resultsmentioning
confidence: 99%
“…The effects of different crosslinking degrees on the mechanical properties of PU‐D‐x films were investigated, and the results are shown in Figure 3. It can be seen that as the amount of crosslinking agent increased from 0.3% to 1.2%, the tensile strength of PU increased from 3.11 to 17.08 MPa, while the elongation at break decreased from 1350% to 669%, this is because that higher cross‐linking degree increases the cohesive energy density, restricts the mobility of polymer chains and limits the deformation and destruction of polymer chains, which leads to the deformation and destruction of PU requires greater external force 26,27 …”
Section: Resultsmentioning
confidence: 99%
“…The tensile strength of polyurethane films with different crosslinking degree showed an increasing tendency, when the TMP content varied from 0 to 1.5 wt%, the tensile strength of the polyurethane films increased from 28 to 34 MPa, respectively. It is known to us that crosslinking increases the cohesive energy density, restricts the mobility of polymer chains, and limits the deformation and destruction of polymer chains and thus lead to an increase in T g , which is beneficial to enhance the mechanical strength 45–47 . In order to further elucidate the relationship between cross‐linking degree and mechanical properties of film, DSC and DMA measurement were employed to characterize their difference (Figure 4b and Figure 5).…”
Section: Resultsmentioning
confidence: 99%
“…It is known to us that crosslinking increases the cohesive energy density, restricts the mobility of polymer chains, and limits the deformation and destruction of polymer chains and thus lead to an increase in T g , which is beneficial to enhance the mechanical strength. [45][46][47] In order to further elucidate the relationship between cross-linking degree and mechanical properties of film, DSC and DMA measurement were employed to characterize their difference (Figure 4b and Figure 5). It was found that the T g increased with the increase in the amount of cross-linking agent.…”
Section: Effect Of Cross-linking Degree On the Tensile Strength Of Shwpumentioning
confidence: 99%